Teinobasis fatakula sp. nov. (Zygoptera: Coenagrionidae), found on ‘Eua Island, Kingdom of Tonga - Marinov, Milen; Donnelly, Thomas (Zootaxa, 2013)
A recent study of the ’Eua Island in the Kingdom of Tonga has yielded a small Odonata fauna including the new species Teinobasis fatakula (Holotype ♂: Kingdom of Tonga, ‘Eua Island, 21.3781o S, 174.9346o W, elevation 175 m; 14 July 2012, M. Marinov leg.). Because ’Eua has aquatic habitats unique within the Kingdom of Tonga, the new species is very likely endemic to that island and represents an extension of the verified range of the genus of at least 2800 km.